THE INFLUENCE OF RECRUITMENT PROCESS ON PERFORMANCE OF NEW EMPLOYEES AT 5 STAR HOTEL JAKARTA: THE INFLUENCE OF RECRUITMENT PROCESS ON PERFORMANCE OF NEW EMPLOYEES AT 5 STAR HOTEL JAKARTA - Fathin, Amirah; Ningrum, Lestari; Abas, Ahmad Junaedi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACT This study examines the effects of the recruitment process to performance at 5 Star Hotel Jakarta. Recruitment process is an independent variable, performance is dependent variable. Explanatory research with descriptive and correlation method is new employees. The number of sample is 101 respondents. The purposive sampling technique is applied with criteria at 5 Star Hotel Jakarta. Data are collected with questionnaires and processed with data analysis. These results indicate that the reliability test was very high (0.880) and based on 22 instruments statement only 1 was invalid. It showed that 101 new employees as respondents consistently answered because they understood and experienced. Each variable has an average value of 4.11 for the recruitment process that is important for new employees and 4.16 for performance that is well. The recruitment process has a low correlation with performance is 0.329. The recruitment process also has a little effect on performance is 10.8%. Based on these results, This 5 Star Hotel should improve the recruitment procedure, increase a conducive, and comfortable working atmosphere.